perbedaan PERBEDAAN VARIASI NILAI TIME REPETITION (TR) 3440ms DAN 3470ms TERHADAP KUALITAS CITRA MRI KNEE JOINT DIRUMAH SAKIT DAERAH MANGUSADA BADUNG - risa, Risa Humairoh; I Kadek Yuda Astina; Nyoman Supriyani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Differences in Time Repetition (TR) value variations on the quality of MRI Knee Joint images using TR 3440 ms and 3470 ms at the Radiology Installation of the Mangusada Regional Hospital, Badung. TR is a parameter that controls the amount of longitudinal magnetization that is recovered before the next RF pulse. The purpose of the study was to determine the comparison of the optimal value and value for the Signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR) on the MRI Knee Joint examination using variations of TR 3440 ms and 3470 ms.This type of research is a quantitative experimental approach. This study consists of 10 data samples. Assessment was carried out on the overall knee joint and anatomical criteria including bone, posterior cruciate ligament, cartilage, and meniscus. Then, the data we tested by Paired T-test.The test results stated that there was no significant difference in the value of the SNR and CNR on the Knee Joint examination using the TR variation of 3440 ms and 3470 ms as indicated by value > 0.05 both Knee Joint anatomical criteria nor as a whole. This is adjusted to the results of the calculation of the average SNR value which is at TR 3440 ms 17.4421 and at TR 3470 ms 16.8784. While CNR, there is no significant difference indicated by value > 0.05, with an average value at TR 3440 ms 17.2311 and at TR 3470 ms 17.8681.There is no significant difference in quality of MRI Knee Joint image with variations of TR 3440 ms and TR 3470 ms. The optimal TR variation that produces SNR MRI Knee Joint image quality is TR 3440 with an average SNR value of 17.4421, and the CNR image quality produces an average value of 17.8681 using TR 3470 ms variation.